Withdrawing or Withholding Treatment - Hassan, Chamsi Pasha; Ali, Albar Mohammed (International Journal of Human and Health Sciences (IJHHS), 2018)
Muslims believe that all healing comes from God, so they have the obligation to search out medical care and right to receive appropriate medical treatment. Islam considers disease as a natural phenomenon and a type of tribulation that expiates sin. Unfortunately many elder patients with chronic illness spend their last few weeks or months in hospitals. Life support is not required if it prolongs the agony and suffering associated with final stages of a terminal illness. The decision to withhold life support from a patient in the intensive care unit (ICU) is a modern medico-legal issue. When considering end-of-life decision making, both withholding and withdrawing life support are considered to be ethically and legally equivalent. Islamic law permits withdrawal of futile treatment on the basis a clear medical decision by at least three Physicians. International Journal of Human and Health Sciences Vol. 01 No. 02 July’17. Page : 59-64